Moderate Aortic Stenosis: What is it and When Should We Intervene? - Badiani, Sveeta (Interv Cardiol, 2021)
Current guidelines recommend aortic valve replacement in patients with severe aortic stenosis in the presence of symptoms or a left ventricular ejection fraction <50%. However, patients with less than severe aortic stenosis may also experience symptoms and recent literature suggests that the prognosis is not as benign as previously reported. There are no recommendations for patients with moderate aortic stenosis and left ventricular dysfunction, despite the high associated morbidity and mortality. There is also some evidence that these patients may benefit from early aortic valve intervention. It is recognised that aortic stenosis not only affects the valve but also has a complex myocardial response. This review discusses the natural history of moderate aortic stenosis along with the role of multimodality imaging in risk stratification in these patients.